The Historiographical Writing in La Florida by Inca Garcilaso de la Vega (ALPHA. Journal of Arts, Literature and Philosophy, 1999)
This article examines La Florida by Inca Garcilaso de la Vega. It aims at showing how in his act of writing the Inca reduces his writing role to that of a copyist, and, at the same time, he becomes a witness as his own writing. Thus, by studying the writing technique used in La Florida we get to know his knowledge about the art of narrating. This allows us to reflect on the historical discourse, the passing of time in human existence, and the cross-disciplinary textual processes involved in creating narrative and historiographic texts.